Markov-based deterioration prediction and asset management of floodway structures. Issue 6 (2nd November 2022) - Tran, Huu; Lokuge, Weena; Karunasena, Warna; Setunge, Sujeeva
ABSTRACT: Floodway structures are sections of roads that have been designed to be overtopped by floodwater and to fully return to serviceable level after the flood water recedes. They are an alternative cost-effective solution to bridges and culverts while they play a significant role in the economy of a country by connecting regional communities, farmlands and agricultural areas to urban cities. To support proactive asset management of floodway structures, this study developed a Markov deterioration model to predict the rate of deterioration for a network of floodway structures by using their visual inspection data. A computational algorithm has also been developed for estimating the lowest-cost inspection interval for floodway structures. A case study with real floodway structures is used to demonstrate its practical application. Effects of maintenance assumption, traffic count and underneath drainage culverts on deterioration rate of floodway network together with a budget estimation are the outcomes of this study.